2010
DOI: 10.1007/s10722-010-9546-8
|View full text |Cite
|
Sign up to set email alerts
|

The Frankincense tree (Boswellia sacra, Burseraceae) from Oman: ITS and ISSR analyses of genetic diversity and implications for conservation

Abstract: DNA sequences from the ITS region of the nuclear genome and Inter-Simple Sequence Repeat markers (ISSR) were used to estimate genetic diversity among and within populations of the Frankincense tree Boswellia sacra from Dhofar, Oman. This is a culturally and ecologically relevant species that is showing symptoms of decline due to anthropic factors and, possibly, global warming. ITS sequences were 511 bp long and showed low (6.4%) variation among geographically different populations. The four selected ISSR prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…in the family of Burseraceae. The genus Boswellia comprises 19 different species (Eslamieh, 2011), whose phylogenetics and taxonomy is still subject of research and scientific discussion (Coppi et al, 2010;Thulin et al, 2008;Thulin and Warfa, 1987;Weeks et al, 2005). The habitat of this genus extends from central to eastern Africa with species like Boswellia frereana Birdw., Boswellia papyrifera Hochst., Boswellia neglecta S. Moore and many more.…”
Section: Introductionmentioning
confidence: 99%
“…in the family of Burseraceae. The genus Boswellia comprises 19 different species (Eslamieh, 2011), whose phylogenetics and taxonomy is still subject of research and scientific discussion (Coppi et al, 2010;Thulin et al, 2008;Thulin and Warfa, 1987;Weeks et al, 2005). The habitat of this genus extends from central to eastern Africa with species like Boswellia frereana Birdw., Boswellia papyrifera Hochst., Boswellia neglecta S. Moore and many more.…”
Section: Introductionmentioning
confidence: 99%
“…As a major consideration when designing the experiment was to mimic the natural sprouting environment of the seeds through using leaf litter and terrariums to resemble the more humid coastal mountain regions of Yemen and Oman, it was not so surprising to find field investigations in that area revealed that altitude showed an effect on the regeneration rate of wild stand of B. sacra (Rafaelli, 2003). Indeed, while also not very genetically diverse, the "Wadi Dowkah Frankincense Park'' which was recognized as a World Heritage Site by UNESCO in 2000(World Heritage, 2016, currently has an ongoing program of germplasm conservation and restoration, and is "considered as the most representative Frankincense site in Oman" (Coppi et al, 2010). This park is at an elevation of 680 to 550 m above sea level, spans for 6 to 7 km 2 , and contains about 1,200 trees, some of which are centenarian, and noted as showing "an impressive branching architecture" as they branch very close to ground level (Raffaelli, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted an extremely low germination rate (<10%), slow seedling growth rate, and difficulty regenerating Boswellia species in both wild and cultivated stands due to intensive tapping to harvest resin, human-induced fire, overgrazing, low genetic variability, lack of dormancy and climatic anomalies (Coppi, 2010;Negussie et al, 2008). These trees have made important contributions to the field of medicine from ancient times to modern research due to a multiplicity of medicinal effects of the tree products including anti-inflammatory, anti-oxidant, antiulcer, anti-arthritic, anti-asthmatic, anti-artherosclerotic, anti-cancer, anti-diarrhoeal, hepatoprotective, antimicrobial, anti-hyperglycemic, diuretic and analgesic influences (Navdeep et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A breeding-oriented perspective suggests reinforcement of the impoverished population by introducing plants from other sites to enrich the genetic basis of the population. This strategy may reduce the risk of genetic drift and, ultimately, may help offset the negative effects of habitat change (Coppi et al, 2010). On the other hand, from a conservation perspective, the reintroduction would be better undertaken using the local seed sources in the ex-situ seed bank which are more likely to exhibit increased fitness over non-local genotypes (Xiao et al, 2006).…”
Section: Insight Into Population Conservationmentioning
confidence: 99%